Fiber analysis vignettes: Electron microscopy to the rescue!. (3rd May 2016) - Roggli, Victor L.
ABSTRACT: There has been considerable interest in the exposure doses that contribute to the various asbestos-associated diseases. Epidemiological studies have shown important differences in the contributions of the various fiber types to asbestos-related diseases, with the amphiboles showing a greater degree of potency as compared to chrysotile. However, epidemiological studies have occasionally provided misleading results. Over the past several decades, there have been several examples where fiber analysis using electron microscopy produced unexpected results which were important to our understanding of disease–exposure relationships. It is the purpose of this article to summarize these fiber analysis vignettes.